Foreign language textbook as a methodological and technological phenomenon: axiological dimension - Natalya Galskova; Zinaida Nikitenko (ARPHA Proceedings, 2021)
The article considers the functions, structure and content of a foreign language textbook in terms of axiological measurement of modern education. The article gives a new understanding of a textbook as a tool to design and realize the content components of language education. A textbook is supposed to provide socio-linguo-cognitive aspects of communication and cognition in a foreign language. The authors pay special attention to the determination of axiologically significant parameters of the praxe-methodological aspect of the textbook content. The textbook’s content through linguistic culture has to form a student’s personality, which realizes itself as a bearer of national values, accepts the equality of different cultures and perceives cultural diversity as a source of not only social, but also personal progress.